PELAKSANAAN HIBAH DAN WASIAT DIKALANGAN MASYARAKAT KABUPATEN BONE - Supandi Patampari, Supandi (Pasca Sarjana STAIN Watampone, 2016)
This study aims to determine theconstruction of the implementation ofthe grant and will among people inBone regency, to know how the form ofgrants and wills, strategies communitiesin the implementation of the grant andthe will and the reason people districtsBone is using grants and wills in thedivision of inheritance compared withthe Islamic inheritance system in Boneregency.